Village Fund Accounting Model in Realizing Nagari Financial Accountability - Armel Yentifa; Wiwik Andriani; Syafira Ramadhea Jr; Dandi Aprila; Gusmita Sofia (Ilomata International Journal of Tax and Accounting, 2023)
This study aims to create an accrual-based accounting model for the Nagari Government. The research method used in obtaining data is observation and interviews while analyzing data using qualitative analysis, namely analysis using an accrual-based accounting model based on Minister of Home Affairs Regulation Number 20 of 2018 concerning the Application of Accrual-Based Government Accounting Standards in village financial management. The analysis results show that since issuing Minister of Home Affairs Regulation Number 20 of 2018 concerning the Application of Accrual-Based Government Accounting Standards in Village Financial Management until the end of 2022, it has not been optimal in preparing accrual-based Nagari Government financial reports. This happens because the apparatus resources must still be ready to implement accrual-based accounting. In addition, the formats used as tools in accrual-based accounting records are more complete, so it is necessary to design a model that the village apparatus can understand. It is hoped that through this research, the implementation of accrual-based accounting can be further improved so that accountability in managing village funds can be achieved as expected.